Immune infiltrates in patients with localised high-risk soft tissue sarcoma treated with neoadjuvant chemotherapy without or with regional hyperthermia: A translational research program of the EORTC 62961-ESHO 95 randomised clinical trial. (November 2021) - Issels, Rolf D.; Noessner, Elfriede; Lindner, Lars H.; Schmidt, Michael; Albertsmeier, Markus; Blay, Jean-Yves; Stutz, Emanuel; Xu, Yujun; Buecklein, Veit; Altendorf-Hofmann, Annelore; Abdel-Rahman, Sultan; Mansmann, Ulrich; et al.
Abstract: Background: The EORTC 62961-ESHO 95 randomised trial showed improved long-term survival of patients with high-risk soft-tissue sarcoma by adding regional hyperthermia to neoadjuvant chemotherapy. We hypothesised that immune infiltrate of patients treated with neoadjuvant therapy associate with clinical outcome. Methods: Tumour infiltrating lymphocytes (TILs) and CD8, FOXP3, PD-1, and PD-L1 were evaluated in sequential biopsies of patients after four cycles of therapy. Results: From a subgroup of 109 patients who had been randomised between July 1997 and November 2006 to neoadjuvant chemotherapy (53 patients) or neoadjuvant chemotherapy with regional hyperthermia (56 patients), 137 biopsies were obtained. TILs increased in paired second biopsies independent of treatment allocation (p < 0.001). FOXP3 regulatory T cells decreased (p = 0.002), and PD-L1 expression of tumours became undetectable. In the multivariate analysis, post-treatment high TILs correlated to LPFS (HR: 0.34; 95% CI 0.15–0.75; p = 0.008) and DFS (HR: 0.38; 95% CI 0.17–0.82; p = 0.015). In comparing post-treatment immune infiltrate between treatment arms, tumour response was associated with neoadjuvant chemotherapy with regional hyperthermia (p = 0.013) and high TILs (p = 0.064). High CD8 cell infiltration was associated with improved LPFS (HR: 0.27; 95% CI 0.09–0.79; Log-rank p = 0.011) and DFS (HR: 0.25; 95% CI 0.09–0.73; Log-rank p = 0.006). Improved survival at 10 years was associated with immune infiltrate after neoadjuvant chemotherapy with regional hyperthermia. Conclusion: Preoperative therapy re-programs a non-inflamed tumour at baseline into an inflamed tumour. The post-treatment immune infiltrate became predictive for clinical outcomes. The combination with regional hyperthermia primes the tumour microenvironment, enabling enhanced anti-tumour immune activity in high-risk soft tissue sarcomas. Trial registration: ClinicalTrials.gov, NCT00003052. Highlights: Preoperative therapy turned the non-inflamed tumour into an immune infiltrated tumour. Immune infiltrate associated with response and survival when hyperthermia was added. Neoadjuvant chemotherapy with hyperthermia primed an anti-tumour microenvironment.